Penilaian Untuk Tujuan Perpajakan Lainnya: Penentuan Harga Limit Lelang Kendaraan Bermotor - Maya Anita (Polytechnic of State Finance STAN, 2022)
Valuation for tax purposes not only plays a role in extracting tax potential but can also be used for other tax activities, such as in determining auction limit prices related to tax collection activities. This study aimed to analyze the implementation of the assessment in determining the limit price of motor vehicle auctions carried out by the Appraiser at KPP Pratama Surabaya Mulyorejo. This research uses a qualitative descriptive approach through library research and field research. The results of this study describe a series of assessment processes in determining the limit price. The stages of the assessment carried out are problem identification, data collection and selection, data analysis, valuation approach, value reconciliation and value conclusion, and assessment reporting. If the assessment is carried out on motorized vehicles used for public transportation, adjustments are also made to the cost factor incurred for obtaining a letter of recommendation from the Ministry of Transportation. One of the suggestions that the author conveys is that the Directorate General of Taxes establish regulations regarding the determination of the discount factor used to determine the liquidation value so that it can be used as the basis for appraisers in making adjustments. Keywords: valuation, auction, discount factor, tax